EVE online is not for everyone: Exceptionalism in online gaming cultures - Bergstrom, Kelly (Human Technology, 2019)
EVE Online is a space-themed massively multiplayer online game that has developed a reputation for being difficult and unwelcoming to new players. In this article, I explore how an emphasis on exceptionalism is present throughout discussions about EVE by its developer, the enthusiast gaming press, and survey responses of current players (N = 647). Taken together, information from these sources reinforces a public perception that EVE is a game that is of interest only to a very specific kind of player. In turn, these findings add further evidence to the long-argued position of feminist game scholars: Not all gaming communities are open to all players. Rather, who plays, what they play, when they play, and/or how often they play is shaped by the larger social context in which play occurs.